Peningkatan Kinerja Administrasi Melalui Aplikasi E-Office - Ahmad Rizqy Hamdy; Budiman Budiman; Reni Nursyanti; Elia Setiana (Universitas Informatika dan Bisnis Indonesia, 2024)
Agency administration plays an important role in various information services and data management, which often causes a waste of time and energy. Currently, many government agencies and organizations have implemented E-office, FTI (Faculty of Technology and Informatics) as one of the faculty at the University of Informatics and Business Indonesia (UNIBI) also faces challenges in carrying out administrative processes. The purpose of this research is to simplify the administrative process that runs in FTI by designing and building E-Office applications. The design stage uses the Waterfall method with 6 (six) UML (Unified Modeling Language), namely use case, class, package, component, sequence, and activity. The development stage uses the Laravel 10 framework and MySQL. Testing this application using Black-Box Testing. The result of this research is the making of a web-based E-Office application that can simplify the administrative process that runs at FTI.